Dual-specificity phosphatase 3 deletion promotes obesity, non-alcoholic steatohepatitis and hepatocellular carcinoma - Sophie Jacques (Nature Portfolio, 2021)
Abstract Non-alcoholic fatty liver disease (NAFLD) is the most common chronic hepatic pathology in Western countries. It encompasses a spectrum of conditions ranging from simple steatosis to more severe and progressive non-alcoholic steatohepatitis (NASH) that can lead to hepatocellular carcinoma (HCC). Obesity and related metabolic syndrome are important risk factors for the development of NAFLD, NASH and HCC. DUSP3 is a small dual-specificity protein phosphatase with a poorly known physiological function. We investigated its role in metabolic syndrome manifestations and in HCC using a mouse knockout (KO) model. While aging, DUSP3-KO mice became obese, exhibited insulin resistance, NAFLD and associated liver damage. These phenotypes were exacerbated under high fat diet (HFD). In addition, DEN administration combined to HFD led to rapid HCC development in DUSP3-KO compared to wild type (WT) mice. DUSP3-KO mice had more serum triglycerides, cholesterol, AST and ALT compared to control WT mice under both regular chow diet (CD) and HFD. The level of fasting insulin was higher compared to WT mice, though, fasting glucose as well as glucose tolerance were normal. At the molecular level, HFD led to decreased expression of DUSP3 in WT mice. DUSP3 deletion was associated with increased and consistent phosphorylation of the insulin receptor (IR) and with higher activation of the downstream signaling pathway. In conclusion, our results support a new role for DUSP3 in obesity, insulin resistance, NAFLD and liver damage.